2020
DOI: 10.1001/jamasurg.2019.5420
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Reproductive Hazards for Female Surgeons in the Operating Room

Abstract: emale surgeons have been found to have high rates of adverse pregnancy outcomes and infertility. [1][2][3] A survey of 1021 US female surgeons across different specialties found an overall pregnancy complication rate of 35.3%, compared with 14.5% in the general population. 3 Other studies support this finding, with a complication rate of 25.3% identified in a survey of 163 female urologists. 2 High infertility rates in surgeons have also been described. 1,3,4 A total of 32% of respondents to the 2012 survey re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 57 publications
1
47
0
Order By: Relevance
“…A meta-analysis investigated the exposure of nurses to anesthetic gases in operating rooms and showed a significant risk of miscarriage. 11 Anderson and Goldman 12 published a review that demonstrated the occurrence of numerous occupational risks in a surgical center that can influence adverse pregnancy outcomes and increase the infertility rate. According to Haffner et al, 13 the results of most studies of pregnant women in contact with formaldehyde suggest that, by avoiding contact during pregnancy, there may be a reduction in the relative risk of low birth weight, miscarriage, and malformations.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis investigated the exposure of nurses to anesthetic gases in operating rooms and showed a significant risk of miscarriage. 11 Anderson and Goldman 12 published a review that demonstrated the occurrence of numerous occupational risks in a surgical center that can influence adverse pregnancy outcomes and increase the infertility rate. According to Haffner et al, 13 the results of most studies of pregnant women in contact with formaldehyde suggest that, by avoiding contact during pregnancy, there may be a reduction in the relative risk of low birth weight, miscarriage, and malformations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, as noted earlier, there are hazardous substances in surgical smoke that are known to be potentially carcinogenic, mutagenic and teratogenic and there is emerging evidence that surgical smoke could also be contributing to adverse pregnancy outcomes and increased rates of infertility in female surgeons. 38 Ultimately, there is an absence of definitive evidence and in this case must be inferred from animal studies and its effects in other contexts. Nevertheless, it remains plausible that chronic exposure to surgical smoke that is not evacuated at the operative site could contribute to female infertility and pregnancy complications.…”
Section: Beneficencementioning
confidence: 99%
“… 22 Surgical masks, even if correctly worn, can only efficiently filter out particles greater than 5 μm in size, thus making filtration of ultrafine particles, including viral particulate, difficult. 23 25 …”
Section: Surgical Smoke and Ultrafine Particlesmentioning
confidence: 99%